Sex Differences in Chronic Postsurgical Pain after Open Thoracotomy - Roca, Gisela; Sabate, Sergi; Serrano, Ancor; Benito, María Carmen; Pérez, María; Revuelta, Miren; Lorenzo, Ana; Busquets, Jordi; Rodríguez, Gema; Sanz, David; Jiménez, Anabel; Parera, Ana; et al. (Journal of cardiothoracic and vascular anesthesia, 2024)
•The incidence of chronic postsurgical pain is higher in women after thoracotomy.•Women's mental state, depression, and catastrophizing scores were worse at baseline.•Presurgical pain prevalence was higher in women.•Pain intensity after thoracotomy did not differ between men and women.•Mental scores worsened in men with chronic pain but improved in women. To determine the incidence of chronic postsurgical pain (CPSP) in women after open thoracotomy. Secondary objectives were to compare relevant patient and procedural variables between women and men. Observational cohort study. Ten university-affiliated hospitals. Ninety-six women and 137 men. Scheduled open thoracotomy. Pain histories, psychological measures, and perceived health status and catastrophizing scores were obtained. The diagnosis of chronic postsurgical pain was by physical examination at 4 months. Standard preoperative, intraoperative, and postoperative data were also recorded. The chronic postsurgical pain incidence was significantly higher in women (53.1%) than in men (38.0%) (p = 0.023). At baseline, women had significantly worse scores on psychological measures (perception of mental state [p = 0.01], depression [p = 0.006], and catastrophizing [p < 0.001]). Women also reported more preoperative pain in the operative area (p = 0.011) and other areas (p = 0.030). These findings show that the incidence of physician-diagnosed chronic postsurgical pain is higher in women than in men after surgeries involving thoracotomy. Sex and gender should be included in future clinical research on pain in surgical settings.